2021
DOI: 10.1021/acschemneuro.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibitors of Amyloid-β and Tau Aggregation with Amyloid-β Disaggregating Properties: Extended In Cellulo, In Silico, and Kinetic Studies of Multifunctional Anti-Alzheimer’s Agents

Abstract: In Alzheimer’s disease, neurons slowly degenerate due to the accumulation of misfolded amyloid β and tau proteins. In our research, we performed extended studies directed at amyloid β and tau aggregation inhibition using in cellulo ( Escherichia coli model of protein aggregation), in silico , and in vitro kinetic studies. We tested our library of 1-benzylamino-2-hydroxyalkyl multifunctional anti-Alzheimer’s agents and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…It was also observed that injecting α-syn monomers exogenously in mice promoted faster aggregation of IAPP, whereas IAPP amyloid formation was reduced in mice lacking the gene encoding α-syn [ 191 ], further implying the cross-seeding interaction between α-syn and hIAPP. Recently, it was reported that the octapeptide TKEQVTNV from α-syn can cross-seed with hIAPP monomers and facilitate hIAPP fibrillation [ 192 ]. Moreover, the cross-seeding between the octapeptide from α-syn and hIAPP could increase cell viability and reduce cell apoptosis by reducing hIAPP induced cytotoxicity [ 192 ], suggesting a broader impact of cross-seeding.…”
Section: Cross-seeding Of Amyloid Proteins: Role and Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also observed that injecting α-syn monomers exogenously in mice promoted faster aggregation of IAPP, whereas IAPP amyloid formation was reduced in mice lacking the gene encoding α-syn [ 191 ], further implying the cross-seeding interaction between α-syn and hIAPP. Recently, it was reported that the octapeptide TKEQVTNV from α-syn can cross-seed with hIAPP monomers and facilitate hIAPP fibrillation [ 192 ]. Moreover, the cross-seeding between the octapeptide from α-syn and hIAPP could increase cell viability and reduce cell apoptosis by reducing hIAPP induced cytotoxicity [ 192 ], suggesting a broader impact of cross-seeding.…”
Section: Cross-seeding Of Amyloid Proteins: Role and Mechanismmentioning
confidence: 99%
“…Recently, it was reported that the octapeptide TKEQVTNV from α-syn can cross-seed with hIAPP monomers and facilitate hIAPP fibrillation [ 192 ]. Moreover, the cross-seeding between the octapeptide from α-syn and hIAPP could increase cell viability and reduce cell apoptosis by reducing hIAPP induced cytotoxicity [ 192 ], suggesting a broader impact of cross-seeding.…”
Section: Cross-seeding Of Amyloid Proteins: Role and Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…After years of failing to find a suitable therapeutic drug against AD, researchers are still using historically established assays, such as MTT, Thioflavin S staining or fluorescence intensity based aggregate counting to validate their in vitro or in silico hits. 53, 54, 55 The unified fluorescence lifetime screening system described in this work overcomes this historical burden and bridges the gap that intrinsically exists between in vitro and in vivo approaches, permitting results from a medium-throughput microfluidic screen to be directly compared to physiologically relevant cellular and whole organism analysis.…”
Section: Implications and Conclusionmentioning
confidence: 99%